2005
DOI: 10.1109/led.2004.840707
|View full text |Cite
|
Sign up to set email alerts
|

An abrupt InP-GaInAs-InP DHBT

Abstract: We report on the performance of abrupt InP-GaInAs-InP double heterojunction bipolar transistors (DHBTs) with a thin heavily doped n-type InP layer at the base-collector interface. The energy barrier between the base and the collector was fully eliminated by a 4-nm-thick silicon doped layer with = 3 10 19 cm 3 . The obtainedand MAX values at a current density of 1 mA/ m 2 are comparable to the values reported for DHBTs with a grade layer between the base and the collector.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…The present results confirm the potential of abrupt InP/InGaAs/InP DHBTs [8]. The barrier between the base and the collector is drastically reduced, if not, eliminated by inserting a δ-doped n-type InP at the BC junction.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The present results confirm the potential of abrupt InP/InGaAs/InP DHBTs [8]. The barrier between the base and the collector is drastically reduced, if not, eliminated by inserting a δ-doped n-type InP at the BC junction.…”
Section: Discussionsupporting
confidence: 85%
“…The total collector layer thickness is ∼104 nm. As shown in [8], thin highly doped layers are sufficiently effective to eliminate the energy barrier between the base and the collector of InP/GaInAs/InP DHBTs. The base layer has been doped to ∼5 × 10 19 cm −3 to minimize the base resistance and compositionally graded from the collector toward the emitter.…”
Section: Growth and Fabricationmentioning
confidence: 99%
See 1 more Smart Citation
“…Bipolar transistors having similar structures were demonstrated that exhibit cutoff frequency in the range of ∼100 GHz [24], [25], though the high frequency operation of a transistor having a filament emitter is yet to be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…However, the complicated grading schemes required to reduce the current blocking conduction band discontinuity at the base/collector junction of the type-I DHBT undermine these advantages as the structures are vertically scaled to the dimensions required to achieve state-of-the-art values. The grading schemes required for type-I DHBTs often implement InGaAs spacers [2] or quaternary grading layers [3]; such transition layers are typically 40 to 60 nm thick, and present a limit to vertically scaling the device using collector thicknesses less than 70 nm, though an abrupt type-I design which uses a thin heavily InP layer at the base collector junction to minimize the energy barrier has also been demonstrated at low current densities [4].…”
Section: Introductionmentioning
confidence: 99%